Providing a Model for Promoting the Health Tourism Industry for Tehran Tourists - Samiei, Adeleh; Karimizand, Mahdi; Esmaeilpour , Hasan (Management Strategies and Engineering Sciences, 2024)
The present study was conducted with the aim of developing a model to promote the health tourism industry. The qualitative part of the research was based on grounded theory. Semi-structured interviews were used to collect data, and the data were analyzed using the Strauss and Corbin method and the paradigmatic model. The sampling was done using theoretical sampling and through purposive (judgmental) techniques. According to the systematic model of grounded theory, experts and managers in the field of health tourism, as well as tourists within the tourism industry, were selected as the study population. The results of the data analysis, obtained from interviews during the process of open, axial, and selective coding, led to the creation of a model for promoting the health tourism industry based on grounded theory. Finally, a pattern was identified to provide a model for promoting the health tourism industry. In the quantitative section, due to the unknown population size, the Morgan sampling table was used to select the sample size. Therefore, the sample size was estimated to be 384, and the same number of questionnaires was distributed among tourists using health services in Tehran. Ultimately, 310 completed and valid questionnaires were received. In the quantitative part of the study, in terms of purpose, the research was applied, and in terms of data collection method, it was descriptive and survey-based. Additionally, structural equation modeling (SEM) using Smart PLS software was employed to analyze the data. The quantitative findings of the research show that market attractiveness positively affects the structure and services of health tourism. Furthermore, health tourism services and the structure of health tourism have had a significant impact on value creation. On the other hand, health tourism services and value creation have had a positive effect on health development. Moreover, the results indicated that environmental factors moderate the effect of market attractiveness and structure on the structure of health tourism. The qualitative findings of this study suggest that to promote the health tourism industry, managers should pay close attention to all identified categories and subcategories in this study and possess adequate and sufficient information on each. In addition, this research highlights the need to focus on promoting the health tourism industry. This study contributes to the literature on various aspects and approaches of health tourism and provides future guidelines for researchers. Ultimately, this study leads to implications for the promotion of the health tourism industry and the optimization of this platform.